The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/cancers14051350
|View full text |Cite
|
Sign up to set email alerts
|

Oligometastatic Disease in Non-Small-Cell Lung Cancer: An Update

Abstract: Oligometastatic non-small-cell lung cancer (NSCLC) is a distinct entity that is different from localized and disseminated diseases. The definition of oligometastatic NSCLC varies across studies in past decades owing to the use of different imaging modalities; however, a uniform definition of oligometastatic NSCLC has been proposed, and this may facilitate trial design and evaluation of certain interventions. Patients with oligometastatic NSCLC are candidates for curative-intent management, in which local ablat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 140 publications
0
3
0
Order By: Relevance
“…Generally speaking, the term oligometastatic disease is defined as either a limited number and/or volume of metastatic lesions and applies to a number of different malignancies [ 6 , 7 , 8 ]. Typically, studies defining and evaluating outcomes of patients with oligometastatic disease use their own study-specific definition of oligometastatic disease, which often ranges from 1–5 metastatic lesions.…”
Section: Historical Definition Of Oligometastatic Disease and Relevan...mentioning
confidence: 99%
“…Generally speaking, the term oligometastatic disease is defined as either a limited number and/or volume of metastatic lesions and applies to a number of different malignancies [ 6 , 7 , 8 ]. Typically, studies defining and evaluating outcomes of patients with oligometastatic disease use their own study-specific definition of oligometastatic disease, which often ranges from 1–5 metastatic lesions.…”
Section: Historical Definition Of Oligometastatic Disease and Relevan...mentioning
confidence: 99%
“…In 1995, Hellman and Weichselbaum first proposed oligometastatic disease as a distinct cancer state between locally confined and systemic metastatic disease [ 100 ], which refers to a metastatic tumor with no more than three to five metastases [ 101 , 102 , 103 , 104 , 105 , 106 ]. For these patients, some researchers claim oligometastasis-directed SBRT should be delivered to all tumor lesions to yield efficient tumor control and immune-stimulating effect [ 76 , 107 , 108 ].…”
Section: Clinical Decision Suggestionsmentioning
confidence: 99%
“…One multicenter study showed that, among individuals with non-small cell lung cancer (NSCLC) and bone metastatic lesions, skeletal-related events occurred in 57.7%, median time until first skeletal-related event was six months, and median survival was 9.5 months [3] . Bone metastases can show complications such as pathological fractures, compression of the spinal cord, pain, and hypercalcemia, and skeletal-related adverse events can severely damage patients’ general condition and function [6] .…”
Section: Introductionmentioning
confidence: 99%